Mekanisme Pasar Perspektif Islam - Abd Ghafur (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2019)
The market is a place that has rules that are prepared to exchange property rights and exchange goods between producers and consumers. Islam affirms that the market must stand on the principle of perfect competition. However, that does not mean that freedom is absolute, but freedom is wrapped in a shari’ah frame. The market mechanism in Islam is the existence of market freedom in determining prices. Prices depend on the market. However, Islam does not adhere to market-based prices freely. Islam will intervene when there is a monopoly on the market price. the market mechanism in an Islamic perspective is not only social dimensioned, but also there is a theological element that the market is controlled and supervised by the Shari’a.